Filosofi Tradisi Patuaekkon sebagai Refleksi Nilai-Nilai Kearifan Lokal dalam Pernikahan Etnik Mandailing sebagai Sumber Belajar IPS: The Philosophy of the Patuaekkon Tradition as a Reflection of Local Wisdom Values in Mandailing Ethnic Weddings as a Source for Social Studies Learning - Alwi, Ahmad; Ponidi, Ponidi (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
This study aims to uncover the philosophy contained in the Patuaekkon tradition, which is one of the important stages in the Mandailing wedding procession, while also reflecting the values of local wisdom that can be integrated as a contextual learning resource in Social Studies (IPS) subjects. This study uses a qualitative approach with a case study method. Data collection was carried out through in-depth interviews, participatory observation, and documentation techniques, involving traditional leaders, the bride and groom's families, and cultural actors directly involved in the Patuaekkon procession in the Mandailing region. The results of the study indicate that the philosophy in Patuaekkon not only functions in the socio-cultural order, but also holds strong educational potential. This tradition teaches the importance of social harmony, collective responsibility, and respect for local values and norms as a foundation in community life. The integration of these values in IPS learning not only enriches the teaching material but also fosters students' awareness of cultural identity and strengthens local cultural resilience amidst the flow of globalization that tends to homogenize. Thus, Patuaekkon can be used as an alternative learning resource that is contextual, applicable, and relevant to shape a young generation with character, culture, and a strong understanding of history and society. This research recommends the need for synergy between educators, traditional leaders, and educational institutions to revive local heritage as part of a culture-based learning transformation.